ANALYSIS OF BUSINESS DEVELOPMENT STRATEGY IN PT. PORT OF INDONESIA IV (PERSERO) BIAK BRANCH - Ronaldo Pandean; Abdul Rahman Kadir; H Muh Sobarsyah (Scientia Integritas Utama, 2023)
This study aims to determine the business development strategy at PT. Pelabuhan Indonesia IV (Persero) Biak Branch. The data needed in this research are primary data and secondary data. Primary data was obtained by combining interview, observation and document review methods while secondary data was obtained through document review and literature study. Data analysis went through stages, namely 1) the input stage to the EFE and IFE matrices, 2) Determination of corporate strategy, 3) the decision stage to produce SO, WO, ST, WT strategies and choice of strategy. The results of the study show that 1) based on the internal external matrix, the suggested corporate strategy is a growth strategy as described in square V. This strategy emphasizes expanding the company by taking over the port of Nabire. 2) based on the SWOT matrix, the suggested strategies are a) increasing market share, b) increasing the quality and quantity of human resources, c) increasing good relations with partners, d) increasing the capacity of docks, warehouses and stockpiles, e) adding equipment communication and patrolling, f) procuring and implementing computerized accounting systems g) increasing socialization and promotion, h) preparing feasibility to improve service quality, j) conducting service differentiation,